First clinical results of masticatory reflexometry. - García Moreira, C.; Angeles Medina, F.; García Ruiz, J.; Nuño Licona, A.; Llanos Rivas, R. (Revista Mexicana de Ingenieria Biomedica, 2018)
35 patients with joint dysfunction were studied with the method of complete response to beating within the masteteric EMG. It was found that the condition determines the existence of broad and prolonged potentiation waves. But it is necessary to use auxiliary criteria to overcome the problem that there are different normal forms of response.